Documentação pedagógica e formação inicial de professores: um olhar para as narrativas dos acadêmicos sobre o processo de documentação pedagógica na educação infantil - Santos, Elaine Maria da Silva dos (2020)
This present research focuses on the pedagogical documentation process in the initial formation of teachers in Early Childhood Education. It presents as a guiding question: what are the students' narratives about the process of pedagogical documentation in the supervised oriented internship in Early Childhood Education I of the Pedagogy Course? The process of documenting the daily life of a group composed of 18 students (2 students and 16 schoolgirls), who attended the Learning Unit Internship in Early Childhood Education I of the Pedagogy Course of the Universidade do Sul de Santa Catarina - 2019, in the municipality of Tubarão, south of the state of Santa Catarina. The research path was built along the way, together, researcher and research object and was characterized, in methodological terms, in a qualitative perspective, which has the method as a deviation (BENJAMIN, 1986; PANDINI-SIMIANO; BARBOSA; SILVA, 2018 ), taking the structure of the case studies as a way of articulating the empirical to the theoretical. The research was carried out from February to July 2019 and had as methodological instruments participant observation, written, photographic records, pedagogical documentation and letters written by students at the end of the internship course. In the analysis, there was a commitment to dialogue between different authors and perspectives, such as, for example, Benjamin (1986, 1987a, 2002), Larrosa (1999, 2017, 2018), Rinaldi (2002), Malaguzzi (1999, 2016), Gandini ( 2002), Pandini-Simiano (2010, 2015), Pandini-Simiano, Barbosa e Silva (2018), Ostetto (2012a, 2012b, 2017), Tardif (2014), Pimenta (1997, 2011), Gatti (2002, 2010) , among others. Understanding the pedagogical documentation as a peculiar narrative woven in the meeting between adults and children, when following the process of documenting with students who work in a mandatory internship with very young children in the public network, it was possible to meet challenges that involve the process of documenting, such as the difficulty in looking and listening to children and the diversity of their childhoods; the lack of time and the difficulty in choosing and building a posture of authorship in the woven narratives. Even in the face of challenges, it is possible to find in the documentation an image of a competent and inventive child, who needs time and a powerful space to live his childhood to the full. The possibility of documenting throughout the internship makes it possible to weave an initial training path based on experience, in the encounter between adults and children in educational contexts. An invitation to students to recognize authors and narrators of their own history. Key words: Early Childhood Education. Pedagogical documentation. Initial formation. Internship. Narrative.